Proyecto de Factibilidad para la creación de una Empresa de Elaboración y Comercialización de Jugo a Base de col de Bruselas para personas diabéticas de la Ciudad de Loja - Reyes Jiménez, Gabriela del Cisne (2016)
Diabetes is a disease, a metabolic disorder that is then presented in the pancreas loses the ability to produce insulin (a hormone that is responsible for distributing glucose into cells) and glucose rises to abnormal values. So, "if there is a deficit or a lack of insulin, the body does not get the energy, that's diabetes," says Pasquel. Lack of awareness and a culture of health in the middle has made the disease more aggressively, one of these is diabetes, which according to Miguel Pasquel, president of the Ecuadorian Society of Endocrinology, has exceeded the estimated as submitted levels of incidence in the world, it is predicted that by 2025 there would be more cases, but this is already reflected today. In 2013 4.600 patients with this disease died. In fact, it is the leading cause of death in the country, a study by the INEC (comparing 1997 and 2011), which states that in 1997 killed 1,896 and in 2011, 4,455. A considerable rise completely. Against this background, the objective of this research is to determine the feasibility of creating a producer and marketer processing based Col Brussels for diabetics City Loja juice, the same as trying to use the abundant benefits of this plant to help welfare, nutrition and general health of the consumer. 6 Inductive, deductive and analytical techniques in addition to information such as surveys and interviews the applicants bidders: to conduct research, a methodology based on the different research methods such as applies. The market segment was determined, employing the population of people with diabetes problem of 3959, same that was used to set the sample size of 350 surveys, which were applied in each of the urban parishes of the canton Loja. In addition, two interviews were conducted to collect relevant information on the offer both ALIVINATU as SUPERMAXI. By analyzing obtained from the application of surveys market research that generated the following results were made: the actual and potential plaintiffs constitute the entire population of diabetics in the city of Loja, while actual plaintiffs represent 99% thereof it is corresponding to 3,919 people, with these data effective demand of 407,576 liters per year was obtained. While the analysis of supply generated a result of 84,000 liters in 2015, that make a difference between effective demand and supply unmet demand annual 323,576 liters was obtained. Based on the study of markets, technical study was designed, in which an installed annual 876,000 liters was determined, while capacity utilization is annual 208,800 liters, this production will cover 65% of unsatisfied demand. For that, the company will be located on Avenida Salvador Bustamante Celi, in the Industrial Park of Loja, industry Amable Maria, parish El Valle Region and province of Loja; which meets all the necessary conditions to carry out the process of production and marketing, without there being any setback for it. Legislative, executive, consultant, assistant or 7 support and operational: Likewise, an administrative analysis determined as a Limited Liability Company and a functional organizational structure with the following hierarchical levels was performed. The project reaches an investment of $ 101,824.33 and will be funded by direct contributions from partners of $ 51,824.33 which corresponds to 51% and credit by the National Finance Corporation of 49% equivalent to $ 50,000.00. Finally, by applying financial indicators shows the following results: Net Present Value generated a positive result of $ 223,171.37 which means that the value of the company will increase during operation stage. The internal rate of return is 77.50%, ie, is greater than the interest rate of opportunity (10,50%). Benefit Cost Ratio results in a value of 1.30 means that for every dollar invested in the project will be generated as profit $ 0.30. The project investment will recover in one year and 3 months. The sensitivity analysis indicates that the project supports an increase in costs of 17.8% and a decrease in revenues of 13.6%., which means that the project is viable to run.